Prevention of esophageal strictures after circumferential endoscopic submucosal dissection - Martínek, Jan; Juhas, Stefan; Dolezel, Radek; Walterová, Barbora; Juhasova, Jana; Klima, Jiri; Rabekova, Zuzana; Vacková, Zuzana (Minerva chirurgica, 2018)
Endoscopic submucosal dissection or widespread endoscopic resection allow the radical removal of circumferential or near-circumferential neoplastic esophageal lesions. The advantage of these endoscopic methods is mini-invasivity and low risk of major adverse events compared to traditional esophagectomy. The major drawback of these extensive resections is the development of stricture - the risk is 70-80% if more than 75% of the circumference is removed and almost 100% if the whole circumference is removed. Thus, an effective method to prevent post-ER/ESD esophageal stricture would be of major benefit, because treatment of strictures requires multiple sessions of endoscopic dilatation and may carry a risk of perforation. Moreover, not all strictures are easy to treat and some patients may develop refractory strictures. There are several techniques and methods, which have been tested in both experimental and/or clinical studies but no one has received general acceptance based on results of high-quality evidence. The studies are usually small with a limited number of patients, there is a lack of randomized controlled trials and some techniques have been described only in experimental studies. Thus, prevention of post-ESD strictures remains an unresolved issue. On the other hand, because of the high risk of stricture and partially proven effectiveness of some preventive techniques, a preventive strategy should be considered in patients undergoing extensive ER/ESD in the esophagus. There is, however, no evidence about the superiority or inferiority of a particular preventive strategy compared to other techniques, moreover, there is paucity of data assessing the effectiveness of the combination of different preventive methods. The best preventive strategies known so far include 1) oral or local administration of corticosteroids; and 2) preventive stenting. Other strategies (preventive sessions of endoscopic dilatation or tissue engineering methods) have unproven efficacy or are too demanding for practical use. Nevertheless, the use of (any) preventive strategy after extensive ER/ESD of the esophagus probably reduces the risk of stricture and the number of endoscopic dilatations, therefore, it should be considered in these patients. However, there is a need for high quality evidence as well as for new ideas and approaches to resolve this important clinical problem.
Keywords: ženské pohlaví; Postoperative Complications; Female; stenóza jícnu; Male; lidé; Middle Aged; lidé středního věku; mužské pohlaví; Esophageal Stenosis; pooperační komplikace; Endoscopic Mucosal Resection; Humans; Risk Factors; endoskopická mukózní resekce; rizikové faktory